Moral Dilemmas in Hospitals: Which Shooting Victim Should Be Saved? - Navarick, Douglas J.; Moreno, Kristen M. (Frontiers in Psychology, 2022)
Portrayed as decision-makers in a hospital emergency department, 431 college students made judgments on which of two victims of a mass shooting should receive immediate, life-saving care. Patients differed in ways that could reveal biases, e.g., age (8 vs. 80 years), kinship (stranger vs. cousin), gender (female vs. male), and villain/hero (shooter vs. policeman who stopped him). Participants rated each patient’s moral deservingness and the likelihood they would choose the patient. Deservingness and choice ratings showed young favored over old, cousin over stranger, and policeman over shooter (largest difference). Female and male were judged equally deserving but female was favored for choice. In analogous hospital-room scenarios, with high risk of injury from falling, age bias disappeared and kinship bias was slightly weaker. With low fall risk, age bias reversed and kinship deservingness bias disappeared. Bias decreases when there is a decrease in severity of potential harm to the preferred stakeholder.